Potential Safety Hazard in Terrace Houses with Foundation Grounding Scheme - Toh C.L.; Toh L.S.; Leong K.W. (Institute of Electrical and Electronics Engineers Inc., 2024)
A low value of earth impedance may introduce sufficiently high fault current to activate the overcurrent protective device in order to clear the ground fault. Therefore, majority of the terrace houses projects use common ground slab steelwork as earth electrode to achieve low earth impedance. This earthing system is known as Foundation Grounding Scheme (FGS). However, a major safety concern about this earthing scheme is the AC touch voltage may exceed 50 V if one of the terrace houses is having fault occurrence. Hence, this paper aims to present a field measurement on the potential touch voltage for terrace houses using FGS technique under fault occurrence. The field test results confirmed that all houses which linked together are exposed to same level of potential touch voltage of about 186 V and the fault current is captured as 170 A before fault clearance at the house with fault. 2023 IEEE.